Please unsubscribe, thanks! : how to take back our time, attention, and purpose in a world designed to bury us in bullshit - Gambuto, Julio Vincent (Avid Reader Press, 2023)
"In Please Unsubscribe, Thanks!, Gambuto gives us a radical blueprint for the ways we can take a deep breath, renew, and commit to a life that we really want, individually and collectively, from unsubscribing to emails and automated subscriptions to reevaluating the presence of people and ideas and habits that no longer serve us or make us happy. Infused with the practical advice in James Clear's Atomic Habits and the humor of Sarah Knight's The Life-Changing Magic of Not Giving a F**k, Please Unsubscribe, Thanks! helps us focus on where we find joy in our lives and encourages us to toss out what doesn't bring us joy in this modern world"--